Investigation of students' metacognitive failures in mathematical problem solving based on metacognitive behavior. Issue 3 (February 2019) - Huda, N; Sutawidjaja, A; Subanji, S; Rahardjo, S
Abstract: This article aims to trace the students' metacognitive failures in mathematical problem solving based on their metacognitive behaviors. There are three types of metacognitive failure in mathematical problem solving: metacognitive blindness, metacognitive vandalism and metacognitive mirage. From 20 students taken as research subjects, they were grouped into 2 groups. The first group is students who perform 2 times on the completion of mathematical problem and the second group is students who perform 3 times on the completion of mathematical problem. Research subjects were taken by a person representing each group. Data were collected by using a task sheet where the subject worked with think aloud then followed by interviewing based on the subject's work. The findings in this study indicates that students who perform the completion of mathematical problem for 2 times experienced 6 times successful of metacognitive behavior and 6 times failures of metacognitive behaviors with the tendency to metacognitive vandalism. While students who perform the completion of mathematical problem for 3 times experienced 5 times successful of metacognitive behavior and 13 times failures of metacognitive behavior with the tendency to metacognitive vandalism and metacognitive mirage.